Mechanical stress reduction in a pressurized 2D-FGM thick hollow cylinder with finite length. (June 2017) - Najibi, Amir
Abstract: The material composition evaluation in functionally graded materials is the main concern of a designer to enhance the appropriate functionality of these materials to adopt them in their applications. In this study, new 2D-FGM material model based on the Mori-Tanaka scheme and third order transition function was developed for a thick hollow cylinder with finite length. The cylinder is subjected to the internal or external non-uniform pressure and also the finite element method was performed to analyse axisymmetric elastic stress. It has been demonstrated that the values of the stresses evaluated from external pressure loading were higher than the internal pressure loading ones. Subsequently, the values of Normalized Effective Stress (NES) vs. metallic volume fraction along the horizontal centre line have not been changed significantly by the variation of n z . In addition, the values of the NES which evaluated on the centre point of cylinder wall have been increased by increasing of the n r . Finally, it has been shown in details that the lowest value of the maximum NES was related to the n r = 20 and n z = 0.1 for both internal and external pressure loading. It means that the ceramic 2 (Si3 N4 ) rich cylinder wall has the lowest value of maximum NES. Graphical abstract: Highlights: The new material distributions have been developed based on the Mori- Tanaka scheme and third order transition function. The values of the stresses extracted from external pressure loading were higher than the internal pressure loading ones. The values of NES vs. metallic volume fraction along the HCL have not been changed significantly by the variation of nz . The values of the NES evaluated on the centre point of cylinder wall have been increased by increasing of the nr . The lowest value of the maximum NES was related to the nr = 20 and nz = 0.1 for both internal and external pressure loading.